Recruitment experiences, working conditions abroad and life satisfaction of overseas Filipino Workers returnees in Miag-ao, Iloilo. - Guzman, Cristina D.
This is a descriptive study of OFW returnees and their full cycle of overseas employment, from pre-employment, during employment to post-employment. Mainly, the researchers put emphasis on their recruitment experiences, working conditions abroad and present life satisfaction., The respondents of the study were 38 OFW returnees from 12 barangays of Miag-ao. Out of the total respondents, 31 were males and 7 were females. These workers, either skilled or unskilled, had worked abroad for at least two years contract and had returned home. The researchers used unstructured interview guide in gathering data and Satisfaction With Life Scale to determine the level of satisfaction. Percentage, frequency distribution and average mean were used as tools for analysis. Recruitment experiences talked about the requirements and documents complied with, costs incurred in the process length of time and other problems encountered by the respondents. Working conditions underscored the working hours, employer/official relationship, rule and regulations, workplace, salary and other related problems. It was found out that OFW returnees were generally quite satisfied with their lives.